Marital Satisfaction Among Older Adults Who Married in Old Age in Sanandaj in 2016 - Halime Zarei; Yadollah Abolfathi Momtaz; Robab Sahaf; Mahboube Mehdi (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Marriage in old age is recommended as a way to improve the quality of life and reduce the loneliness of elders; however, studies disregarded measuring the satisfaction of elders who married in old age. Therefore, the present study aimed to determine the marital satisfaction among elders who were married during old ages. Methods & Materials This was a cross-sectional study conducted in Sanandaj City, Iran, in 2015. The convenience sampling method was used. The research participants were 190 people aged  ≥60 years who were married in old ages. The required data were collected by Evaluation and Nurturing Relationship Issues, Communication, and Happiness (Enrich) Marital Satisfaction Scale. The obtained data were analyzed using SPSS, descriptive and analytical statistics, and Independent Samples t-test. Results The Mean±SD age of study participants was 67.37±11.24 years. The Mean±SD marital satisfaction score was 36.95±3.70. More than 60% of the elders who got married in old age reported high and very high marital satisfaction; only 3.7% of them reported low marital satisfaction. The obtained data revealed no significant gender difference in marital satisfaction. Conclusion A high marital satisfaction was reported by the studied elders. These results can be beneficial to encourage single elders to get married in old age.